"But our lights were still on": Decolonizing energy futures emerging from climate finance regulation in Fiji. (February 2021) - Anantharajah, Kirsty
Abstract: The arrival of climate finance on global agendas has spurred the drive towards renewable energy fuelled techno-futures in Fiji and Pacific region. The climate finance phenomenon has also generated significant discursive focus on matters of regulation. Yet despite this salience, there has been little critical examination of regulatory material-discursive practices surrounding energy infrastructure and its financing. In responding to this gap, the paper utilizes an important Science and Technology Studies (STS) perspective, postcolonial science studies, to unpack opaque material-discursive practices surrounding renewable energy and climate finance regulation in Fiji. Drawing on multi-sited ethnographic data, the paper argues that knowledge, relational and material practices surrounding renewable energy regulation and climate finance are opaquely shaping potentially unequal futures in Fiji. The paper highlights material effects of such regulatory practice in Fiji including the sourcing of labour, expertise and agency externally; poor compliance by international financial institutions exhibiting with regulation aimed at supporting local economies and energy transitions; and conditions of under electrification in rural communities. Beneath dominant regulatory discourses and practices, however, are also important contestations for certain socio-technical futures emerging in Fiji. The application of critical perspectives to renewable energy and climate finance regulatory practices is vital in making these lived material consequences, and emerging, contested futures in Fiji visible, to allow for their clearer, and more equitable navigation.